2020
DOI: 10.1101/2020.06.09.20126417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in wastewater in Japan by multiple molecular assays-implication for wastewater-based epidemiology (WBE)

Abstract: Presence of SARS-coronavirus-2 (SARS-CoV-2) in wastewater sample has been documented in several countries. Wastewater-based epidemiology (WBE) is potentially effective for early warning of COVID-19 outbreak. The purpose of this study was to verify the detection limit of WBE for COVID-19. In total, 27 influent wastewater samples were collected from four wastewater treatment plants in Ishikawa and Toyama prefectures in Japan. During the study period, numbers of the confirmed COVID-19 cases in these prefectures i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…The copyright holder for this this version posted September 23, 2020. ; https://doi.org/10.1101/2020.09.21.20197244 doi: medRxiv preprint between 10 2 -10 4 copies•l -1 , and in feces from -10 10 copies•g -1 (Wu et al, 2020;Wurtzer et al, 2020;Wölfel et al, 2020;La Rosa et al, 2020;Farkas et al, 2020;Haramoto et al, 2020;Bhowmick et al, 2020). Taking into account the reported volume of wastewater produced by citizens (from to l), it can be calculated that the lowest detectable infection rate using WBE methods ranges between 10 -1 and 10 -4 % (Hata et al;Wurtzer et al, 2020;Ahmed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this this version posted September 23, 2020. ; https://doi.org/10.1101/2020.09.21.20197244 doi: medRxiv preprint between 10 2 -10 4 copies•l -1 , and in feces from -10 10 copies•g -1 (Wu et al, 2020;Wurtzer et al, 2020;Wölfel et al, 2020;La Rosa et al, 2020;Farkas et al, 2020;Haramoto et al, 2020;Bhowmick et al, 2020). Taking into account the reported volume of wastewater produced by citizens (from to l), it can be calculated that the lowest detectable infection rate using WBE methods ranges between 10 -1 and 10 -4 % (Hata et al;Wurtzer et al, 2020;Ahmed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are additional limitations especially for SARS-CoV-2 viral particle determination, since this virus is an RNA-based one, and therefore RT reaction is included in the determination procedure, and the probability of RT efficiency may also differ depending on many factors. Thus, it has been shown that the detection efficiency of SARS-CoV-2 viral particles ranges from 8.5 to 71.6% depending on the concentration method and the volume of the concentrated sample (Hata et al;Medema et al, 2020;Haramoto et al, 2020;. The results obtained may be dependent on molecular process control that can strongly vary in different lab protocols and influence the final results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, identification and quantification of the viral genome in wastewater can be a reliable indicator of disease prevalence among the communities, as revealed for other similar viruses [46][47][48]. Very recently, studies report detections of RNA of SARS-CoV-2 in wastewater [27,46,[49][50][51][52][53], with detected RNA amount being higher than that expected from reported infection cases. Moreover, SARS-CoV-2 was detected in wastewater 7-10 days earlier than clinically reported cases [46,53,54].…”
Section: Perspectives Of Wastewater-based Epidemiology: Monitoring Comentioning
confidence: 99%
“…Very recently, studies report detections of RNA of SARS-CoV-2 in wastewater [27,46,[49][50][51][52][53], with detected RNA amount being higher than that expected from reported infection cases. Moreover, SARS-CoV-2 was detected in wastewater 7-10 days earlier than clinically reported cases [46,53,54]. In summary, wastewater analysis is recommended as a non-invasive initial-warning tool that can help in monitoring the trend and status of COVID-19 spread and as a device for tweaking public health response [35,55,56].…”
Section: Perspectives Of Wastewater-based Epidemiology: Monitoring Comentioning
confidence: 99%